Large artery disease in patients with cerebral ischaemia: frequency, investigation and management - Marquardt, L; Dr Lars Marquardt (2010)
Stroke is the third leading cause of death in the developed world and is the leading neurological cause of disability with a massive impact on personal life and society. Large artery atherosclerosis is one of the main causes of ischaemic stroke. However, in several aspects of this condition there is still a significant amount of uncertainty about its prevalence, appropriate investigation and possible treatment. Reliable data on epidemiology are therefore necessary to provide clinicians and researchers with crucial information to guide diagnostic and therapeutic management as well as further research. With this thesis I aimed to provide useful information about the prevalence of large artery disease in certain groups of patients, and to contribute to investigation- and managementstrategies using data from a large population based study, the Oxford Vascular Study (OXVASC). OXVASC is a prospective, population-based incidence study of vascular disease in Oxfordshire, UK, which started in 2002 and is ongoing. The study population comprises all 91,106 individuals registered with nine general practices and uses multiple methods of case ascertainment to identify all patients with vascular events. Firstly, I have shown that the prevalence of ≥50% vertebral or basilar artery stenosis in posterior circulation TIA or minor stroke is more than twice as high as the prevalence of ≥50% carotid stenosis in patients with carotid territory events, and is associated with a very high early risk of stroke of 22% and TIA of 46%. Furthermore, severe vertebral and/or basilar artery stenosis is associated with multiple TIAs at first presentation. Secondly, I have shown that early risk of stroke was higher after posterior circulation TIA, with a 1-year risk of 16%, than after carotid territory TIA, with a 1-year risk of 9%. In addition, I was able to show for the first time, that the ABCD2 score was predictive of early stroke not only in patients with carotid circulation TIA but also in patients with vertebrobasilar TIA. Thirdly, in a pilot feasibility study about arterial spin labelling magnetic resonance imaging in patients with large artery disease in the vertebrobasilar circulation I have shown that patients with severe large artery disease have significantly impaired occipital brain perfusion. My results suggest that this new technique might be a useful tool to identify suitable patients for interventional treatment of vertebrobasilar large artery disease. Fourthly, I was able to show that the risk of ipsilateral stroke and TIA in patients with an asymptomatic carotid stenosis is very low with contemporary best medical treatment alone, suggesting that routine carotid endarterectomy for asymptomatic carotid stenosis might not longer be feasible. Finally, I have clarified that lower rates of intervention for moderate to severe symptomatic carotid stenosis in women than in men can be explained by sex-differences in the populationbased incidence of carotid large artery disease and not due to under-investigation or reluctance amongst women to undergo investigation or treatment.